Intravenous immunoglobulin treatment responsiveness depends on the degree of CD8+ T cell activation in Kawasaki disease - Ye, Qing; Gong, Fang-qi; Shang, Shi-qiang; Hu, Jian (Clinical immunology (Orlando, Fla.), 2016)
Kawasaki disease (KD) has become the most common cause of acquired heart disease in children and is also a risk factor for ischemic heart disease in adults. However, Kawasaki disease lacks specific laboratory diagnostic indices. Thus, this study analyzed the T cell activation profiles of Kawasaki disease and assessed their value in the diagnosis of Kawasaki disease and the prediction of intravenous immunoglobulin (IVIG) sensitivity. We analyzed human leukocyte antigen-DR (HLA-DR), CD69 and CD25 expression on peripheral blood CD4+ and CD8+ T cells during the acute phase of KD. We compared the percentages of HLA-DR+/CD69+/CD25+ T cells in the CD4+ and CD8+ T cell populations of IVIG-effective and IVIG-resistant groups. Receiver operating characteristic curves were used to assess the diagnostic value of the above parameters. The median percentage of CD8+HLA-DR+ T cells and the median ratio of CD8+HLA-DR+ T cells/CD8+CD25+ T cells were significantly elevated in the patient group compared with those in the control group during the acute phase of KD. Regarding the diagnosis of Kawasaki disease, the area under the ROC curve was 0.939 for the percentage of CD8+HLA-DR+ T cells. There was a significant difference in the ratio of CD8+HLA-DR+ T cells/CD8+CD69+ T cells between IVIG-resistant patients and IVIG-sensitive patients. Regarding IVIG sensitivity, the area under the ROC curve was 0.795 for it. Excessive CD8+ T cell activation, as well as an imbalance between CD8+ T cell activation and inhibition, underlies the pathogenesis of Kawasaki disease. The percentage of CD8+ HLA-DR+ T cells may be used as an index to diagnose Kawasaki disease. IVIG inhibits CD8+ T cell activation, but excessive CD8+ T cell activation may cause IVIG resistance. The ratio of CD8+HLA-DR+ T cells/CD8+CD69+ T cells may be used as a predictor of IVIG sensitivity. •An imbalance in CD8+ T cell activation and inhibition are important in the pathogenesis of Kawasaki disease.•The percentage of CD8+HLA-DR+ T cells may be used as an index to diagnose Kawasaki disease.•IVIG inhibits CD8+ T cell activation, but if the level of CD8+ T cell activation is too high, IVIG resistance may result.•The ratio of CD3+CD8+HLA-DR+ T cells/CD3+CD8+CD69+ T cells may be used as a predictor of IVIG sensitivity.